URIC ACID LEVELS IN MOTORCYCLE WORKSHOP WORKERS IN PEKANBARU CITY - Alfin Surya; Rekha Astuty; Mega Pratiwi Irawan; Rosa Devitria; Fatma Fatma; Hesti Marliza; Zaiyar Zaiyar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
A byproduct of purine metabolism is uric acid, which can cause hyperuricemia and increase the risk of gout and other metabolic diseases when blood levels are too high. Long-term exposure to lubricants, vehicle exhaust, and carbon monoxide can increase uric acid levels in motorcycle repair workers. The heart and kidneys, which are important for uric acid metabolism and excretion, may be affected by exposure to substances found in motor vehicle lubricants and exhaust fumes. Additionally, the sedentary work habits of workshop workers, which involve little physical activity, can disrupt kidney function and delay the elimination of uric acid from the body. Therefore, due to the combination of lifestyle and work environment characteristics, motorcycle repair shop workers can be considered a high-risk category for developing gout. However, there is still a lack of information about uric acid levels in this population, particularly in Pekanbaru City. The purpose of this investigation is to determine the uric acid levels of employees at motorcycle workshop X in Pekanbaru City. Samples were taken from employees who met the inclusion and exclusion criteria using a descriptive cross-sectional methodology. The Point-of-Care Testing (POCT) approach, along with strip testing, is used to assess uric acid. According to findings from 24 respondents, 3 workers (12.5%) experienced increased uric acid levels, while 21 workers (87.5%) had normal levels. At 5.44 mg/dL, the average uric acid level is within the reference range. These findings indicate that prolonged working hours and occupational exposure elevate the risk of hyperuricemia, despite the majority of employees exhibiting normal uric acid levels. To reduce the burden of metabolic diseases on the high-risk working population, this study emphasizes the importance of occupational health surveillance and preventive measures.Keywords: Uric acid, Motorcycle workshop workers, Hyperuricemia, Occupational exposure.